PERENCANAAN STRUKTUR GEDUNG KULIAH DI YOGYAKARTA - wahyu hardianto; Ario Bimo Hanityo; Himawan Indarto; Ilham Indarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Auniversity building is planned to be built inYogyakarta. The structure of the building is designed to comply with the Indonesian Concrete Code (SNI 03-2847-2002)for Special Moment Resisting Frame System (SMRFS). Dynamic analysis of the structure is based on spectrum method regulated inIndonesian Seismic Code(SNI 03-1726-2012). The structure of this building is designed to followthe Strong Coloumn Weak Beam concept. With this concept, plastic hings are designed to form on beam ends when the structure is hit by earthquake.Thestructural analysis conducted in this project shows that the structure is strong enough to resist earthquake loading.